2010
DOI: 10.15835/nsb224621
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Shoot Regeneration of NAA-Pulse Treated Plumular Leaf Explants of Cowpea

Abstract: Cowpea (Vigna unguiculata L.) is an economically important grain legume crop and is an important source of dietary protein in many of the developing countries. The present study reports the effect of pulse treatment duration, concentration of NAA and presence of NAA in the culture medium on shoot regeneration from plumular leaf explant of Turkish cowpea cv. ' Akkiz' and 'Karagoz' . Pulse treatment of mature embryos with 20 mg l -1 NAA for 1 and 3 weeks followed by culturing of plumular leaf explant on MS mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Pulsing techniques involve reducing the explants' exposure time to growth regulators (Andrade et al 2006;Aasim 2010), minimizing the required time to produce micropropagated plants (Pullman et al 2003;Andrade et al 2006). This study aimed to evaluate the effect of TDZ pulsing on the in vitro peach palm morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsing techniques involve reducing the explants' exposure time to growth regulators (Andrade et al 2006;Aasim 2010), minimizing the required time to produce micropropagated plants (Pullman et al 2003;Andrade et al 2006). This study aimed to evaluate the effect of TDZ pulsing on the in vitro peach palm morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…these genotypes regeneration frequencies decreased when the concentration of BAP were increased (Table 1.0). In SAMPEA 9, however, treatment with BAP had no significant influence on the regeneration frequency (Table 1) regeneration in cowpea was enhanced by preconditioning cotyledons and cotyledonary nodes in high concentrations of BAP ( and Reddy, 1996;al.,1999;Raveendaret al, 2009;, in TDZ (Bakshi et al in NAA (Aasim, 2010). Multiple shoots were also regenerated from embryonic axes of cowpea in the presence of BAP following decapitation to eliminate apical dominance (Popelka 2006;Rajiet al, 2008).Generally, we observed that explant cultured on hormone free medium produced lower percentage regeneration and this observation become clear when comparison of regeneration response in expla hormone free media and those cultured on media containing BAP was made irrespective of the hormone concentration.…”
Section: Resultsmentioning
confidence: 99%